Intermediate system to intermediate system (IS-IS) routing protocol - White, Russ; Safari eBooks ([Place of publication not identified] : Cisco Press, 2016)
"Intermediate System to Intermediate System (IS-IS) Routing Protocol LiveLesson provides networking engineers with a full and complete knowledge of the operation and deployment of IS-IS in a variety of network environments. In this video training, networking expert Russ White provides you with a detailed introduction to the IS-IS routing protocol. IS-IS is a widely deployed protocol used to provide routing information for IPv4 and IPv6 networks as well as MPLS label switching and many advanced functions. This video provides you with everything you need to know to get up and running with IS-IS, from the underlying history to configuration and troubleshooting a wide variety of features."--Resource description page.
Title from title screen (viewed May 6, 2016).
Presenter, Russ White.
Keywords: IS-IS (Computer network protocol); Electronic books